Linguistic studies of the Croatian language in Zagreb - Hoyt, Alexander D. (Array, 1997)
The author gives a critical description of linguistic research on the Zagreb vernacular carried out by Magner, Šojat, and Bauer, and attempts to describe the relationship between three variants that are used in the city: Zagreb Kajkavian, Zagreb Štokavian, and Standard Croatian.